High-Impact Weather Events over the SAARC Region - Ray, Kamaljit; Mohapatra, M.; Bandyopadhyay, B.K; Rathore, L.S (Springer International Publishing : Imprint: Springer, 2015)
This book is a compilation of papers contributed by researchers and scientists from SAARC nations and deals with high-impact weather conditions, their prediction and potential consequences for populations in the SAARC region. There have been a number of recent advances in our understanding and prediction of cyclones, severe thunderstorms, squalls, heat and cold waves, droughts and heavy rainfall, based on the latest observational data and NWP modeling platform. The SAARC region is vulnerable to high-impact weather events because of geographical features like high mountains, plateaus and vast oceans. As our climate continues to change over the coming years, the likelihood of extreme and potentially high-impact weather and climate events will be at its highest when natural and anthropogenic effects combine. All chapters were written by leading experts in their respective research and operational fields. The book reviews the latest research, future needs, forecasting skills and societal impacts of extreme weather events and offers high-quality reference material for weather forecasters, disaster managers and researchers.